Rowing at the 2028 Los Angeles Olympic Games: 1500-m versus 2000-m performance and the predictive accuracy of a critical speed model - Astridge, D. J.; Peeling, P.; Goods, P. S. R.; Girard, O.; Binnie, M. J. (International Journal of Sports Physiology and Performance, 2026)
Purpose: In preparation for the reduced 1500-m-rowing racing distance at the Los Angeles 2028 Olympic Games, we compared performance between maximal 2000-m (TT2000) and 1500-m (TT1500) ergometer time trials and evaluated the predictive accuracy of a linear critical speed (CS) model in elite rowers. Methods: Thirty-four elite under-23 rowers (12 female, 22 male) completed TT2000, TT1500, and 500-m (TT500) maximal ergometer time trials on separate days. Performance differences between TT2000 and TT1500 were assessed using linear mixed modeling. Completion times from TT2000 and TT500 were used in a CS model to predict TT1500 time. Results: Compared with TT2000, mean power output was 4.8% higher in males and 4.4% higher in females during TT1500, with a 26% reduction in completion time across both groups. The CS model using TT500 and TT2000 accurately predicted TT1500 time for both sexes, with a mean absolute error of <1 second, a standard error of estimate of 2.8 seconds, and a coefficient of variation of 0.5%. A near-perfect correlation existed between actual and predicted TT1500 times (R = .99). Conclusions: This simple CS model, based on standard tests, allows practitioners to track 1500-m performance progression without disrupting preparation for 2000-m events, which remain central to international competition throughout the Los Angeles 2028 Olympic Games quadrennial. Performance times in TT1500 indicate that elite rowers likely require further specific preparation to optimize performance over the reduced Olympic racing distance.